An analytical framework to examine shari'ah-compliant mortgage financing by cooperative financial institutions in Malaysia - Zabri, Zaidi; Abdul Razak, Dzuljastri; Mohamed, Mustafa Omar (2014)
This paper presents an analytical framework for exploring and critically examining the supply side’s issues and challenges of offering Shari’ah-compliant mortgage financing by cooperative financial institutions in Malaysia. Concepts from five distinct theories (theory of credit cooperative, transaction costs theory, theory of credit rationing, agency theory, and stakeholder theory) are modified and integrated to form a hybrid, layered framework. It is then used as a ‘lens’ to highlight the issues pertaining to (business models and strategies, good governance, regulation and supervision, risk management, human resource management) which may influence the success of such product. The analytical framework presented is useful for relevant stakeholders within this milieu on how to manage the issues, challenges, and harnessing the prospects of Shari’ah-compliant mortgage financing products.